The environmental and health impacts of tobacco agriculture, cigarette manufacture and consumption - Thomas E Novotny; Stella Aguinaga Bialous; Lindsay Burt; Clifton Curtis; Vera Luiza da Costa; Silvae Usman Iqtidar; Yuchen Liu; Sameer Pujari; Edouard Tursan d'Espaignet (The World Health Organization, 2015)
The health consequences of tobacco use are well known, but less recognized are the significant environmental impacts of tobacco production and use. The environmental impacts of tobacco include tobacco growing and curing; product manufacturing and distribution; product consumption; and post-consumption waste. The World Health Organization's Framework Convention on Tobacco Control addresses environmental concerns in Articles 17 and 18, which primarily apply to tobacco agriculture. Article 5.3 calls for protection from policy interference by the tobacco industry regarding the environmental harms of tobacco production and use. We detail the environmental impacts of the tobacco life-cycle and suggest policy responses.